PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE SUDUT TIMUR - Wanda Pandu Dechlisa Yarsah; Suryani Chodidjah (LPPM Universitas Asa Indonesia, 2025)
This study aims to determine the influence of product quality, promotion, and price perception on consumer purchase decisions at Corner Timur Café. The method used is quantitative method with a survey approach. The population in this study includes all consumers of Corner Timur Café, with a total of 127 respondents selected through purposive sampling during visits to the café in March 2025. Data were collected through the distribution of questionnaires and analyzed using SPSS software version 25. The results showed that product quality and promotion had a positive and significant effect on consumer purchase decisions, while price perception did not have a significant effect. These findings indicate that purchasing decisions are influenced more by the quality of the products offered and the effectiveness of promotions rather than price considerations. Therefore, it is recommended that Corner Timur Café prioritize improving product quality and developing a more attractive promotional strategy to increase consumer appeal and encourage increased sales.